2011
DOI: 10.1002/cphc.201100634
|View full text |Cite
|
Sign up to set email alerts
|

Inhibited Phenol Ionization in Reverse Micelles: Confinement Effect at the Nanometer Scale

Abstract: We found that the absorption spectra of 2-acetylphenol (2-HAP), 4-acetylphenol (4-HAP), and p-nitrophenol (p-NPh) in water/sodium 1,4-bis(2-ethylhexyl)sulfosuccinate (AOT)/n-heptane reverse micelles (RMs) at various W(0) (W(0) = [H(2)O]/[surfactant]) values studied changed with time if (-)OH ions were present in the RM water pool. There is an evolution of ionized phenol (phenolate) bands to nonionized phenol absorption bands with time and this process is faster at low W(0) values and with phenols with higher b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 65 publications
1
34
0
Order By: Relevance
“…2229 The reverse micelles allow for placement of the drug by spectroscopic characterization of the micellar interfaces by changing the ratio of water to surfactant ( w 0 ). 21,22,27,3033 Although this system is powerful in providing the molecular detail, Langmuir monolayers of dipalmitoylphosphatidylcholine (DPPC) are frequently used models of eukaryotic cell membranes. Langmuir monolayers have been used previously for a variety of studies, detailing interactions of lipids with cholesterol, 34 phospholipids, fatty acids, 35 proteins, 36,37 and drugs.…”
Section: Introductionmentioning
confidence: 99%
“…2229 The reverse micelles allow for placement of the drug by spectroscopic characterization of the micellar interfaces by changing the ratio of water to surfactant ( w 0 ). 21,22,27,3033 Although this system is powerful in providing the molecular detail, Langmuir monolayers of dipalmitoylphosphatidylcholine (DPPC) are frequently used models of eukaryotic cell membranes. Langmuir monolayers have been used previously for a variety of studies, detailing interactions of lipids with cholesterol, 34 phospholipids, fatty acids, 35 proteins, 36,37 and drugs.…”
Section: Introductionmentioning
confidence: 99%
“…So there will be more encounters between reactants, but they will be together a shorter time. Micelles were previously described as “supercages” [56], and many studies proved a cage-effect in chemical reactions in micelles [25,57,58]. The hypothesis is that this approach can be used to compare the chemical kinetics in micelles and in a solution, instead of in liquid and in gas phases.…”
Section: Resultsmentioning
confidence: 99%
“…The rate of intermicellar exchange is the same for both metals, so the reason for this different behavior is not obvious. Previous studies suggest that micelles may act as a cage [27,48]. This assumption is based on the well-known cage effect in chemical kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…It is understood that reverse micelles are reaction vessels in which classical assumptions cannot always be used. For example, it was demonstrated that the concept as simple as the classical definition of pH cannot be applied in the interior of reverse micelles [2728]. Previous simulation studies concluded that the structure of nanoparticles obtained in reverse micelles is determined by the difference in the reduction rates only if both reductions occur at the same rate or if reductions have very different rates [23,29].…”
Section: Introductionmentioning
confidence: 99%